Properties of cellulose nanofibre networks prepared from never-dried and dried paper mill sludge. (1st October 2018) - Adu, Cynthia; Berglund, Linn; Oksman, Kristiina; Eichhorn, Stephen J.; Jolly, Mark; Zhu, Chenchen
Abstract: Paper mills yield large volumes of sludge materials which pose an environmental and economic challenge for disposal, despite the fact that they could be a valuable source for cellulose nanofibres (CNF) production. The aim of the study was to evaluate the production process and properties of CNF prepared by mechanical fibrillation of never-dried and dried paper mill sludge (PMS). Atomic force microscopy (AFM) showed that average diameters for both never-dried and dried paper sludge nanofibres (PSNF) were less than 50 nm. The never-dried and dried sludge nanofibres showed no statistical significant difference (p > 0.05) in strength ∼92 MPa, and ∼85 MPa and modulus ∼11 GPa and ∼10 GPa. The study concludes that paper mill sludge can be used in a dried state for CNF production to reduce transportation and storage challenges posed on industrial scale.